Matrix Rigidity-Modulated Cardiovascular Organoid Formation from Embryoid Bodies - Shkumatov, Artem (Public Library of Science, 2014)
Stem cell clusters, such as embryoid bodies (EBs) derived from embryonic stem cells, are extensively studied for creation of multicellular clusters and complex functional tissues. It is common to control phenotypes of ES cells with varying molecular compounds; however, there is still a need to improve the controllability of cell differentiation, and thus, the quality of created tissue. This study demonstrates a simple but effective strategy to promote formation of vascularized cardiac muscle - like tissue in EBs and form contracting cardiovascular organoids by modulating the stiffness of a cell adherent hydrogel. Using collagen-conjugated polyacrylamide hydrogels with controlled elastic moduli, we discovered that cellular organization in a form of vascularized cardiac muscle sheet was maximal on the gel with the stiffness similar to cardiac muscle. We envisage that the results of this study will greatly contribute to better understanding of emergent behavior of stem cells in developmental and regeneration process and will also expedite translation of EB studies to drug-screening device assembly and clinical treatments.